Gastronomy and Tourism: Reflections on local food consumption in urban and rural areas - Introduction - Marujo, Noémi (2019)
Food, gastronomy and tourism is considered a new area of academic interest (Maberly and Reid, 2014; Okumus et al., 2018) and a marker of social distinction (Okumus et al., 2018; Kim et al., 2009). Among the variety of research topics inside the area of tourism and gastronomy, local food consumption still needs further discussion. As highlighted in the literature, the consumption of local food is affected by a number of factors, destination environments, among others, being an example of a dimension that still needs to be discussed. Moreover, consumption of local food in rural and urban areas provides different perspectives in terms of environmental, social and cultural context.